RELEVANSI PENDIDIKAN PSIKOLOGIS PERSPEKTIF ABU ZAID AL BALKHI DENGAN PEMBINAAN PSIKOLOGIS SANTRI DI PONDOK PESANTREN , STUDY KASUS DI PESANTREN DAARUL MUWAHHIDIIN TANAH DATAR - Rinaldo , Doni; Muchtar , Asmaji; Hariyadi, Sugeng; doni rinaldo, doni rinaldo (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the relevance of Abu Zaid al-Balkhi’s psychological educational framework to the psychological education practices implemented at Pesantren Daarul Muwahhidiin, Tanah Datar. As a prominent figure in the classical Islamic psychological tradition, al-Balkhi offers a comprehensive approach to mental health through the concepts of cognitive–emotional balance, internal and external therapies, and preventive measures against psychological disturbances such as anger, acute fear (panic attack), depression, and obsessive–compulsive disorder (OCD). This research employs a qualitative approach using a case study design through observations, interviews, and document analysis. The findings indicate a significant alignment between al-Balkhi’s concepts and the pesantren’s psychological education practices, particularly in emotional regulation, spiritual cultivation, counseling services, and cognitive strategies for managing anxiety and impulsive behavior. The pesantren applies several preventive and interventive measures, including counseling programs, religious instruction, spiritual habituation, Islamic-based cognitive therapy, as well as spiritual practices such as Qur’anic recitation and dhikr. The study concludes that al-Balkhi’s psychological insights are highly relevant and can serve as a foundation for developing an Islamic psychological curriculum, strengthening teacher capacity, and enhancing integrated cognitive–spiritual counseling services in pesantren. This research recommends the development of a systematic Islamic psychology curriculum and further empirical studies on the effectiveness of cognitive–spiritual interventions within Islamic boarding school settings.